2022
DOI: 10.1051/0004-6361/202141928
|View full text |Cite
|
Sign up to set email alerts
|

Search and analysis of giant radio galaxies with associated nuclei (SAGAN)

Abstract: Giant radio quasars (GRQs) are radio-loud active galactic nuclei (AGN) that propel megaparsec-scale jets. In order to understand GRQs and their properties, we have compiled all known GRQs (‘the GRQ catalogue’) and a subset of small (size < 700 kpc) radio quasars (SRQs) from the literature. In the process, we have found ten new Fanaroff-Riley type-II GRQs in the redshift range of 0.66 <  z <  1.72, which we include in the GRQ catalogue. Using the above samples, we have carried out a systematic comparat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 104 publications
1
7
0
Order By: Relevance
“…We stress that, while recent observational efforts are significantly increasing the detection number of giant radio galaxies and giant radio quasars (GRQs) (e.g. Kuźmicz et al 2018;Dabhade et al 2020a,b;Bruni et al 2020;Kuźmicz & Jamrozy 2021;Delhaize et al 2021;Andernach et al 2021;Simonte et al 2022;Mahato et al 2022, Oei et al 2022, the number of giant radio sources identified at redshift z > 1.5 remains to date limited (10/239 in the sample of Dabhade et al 2020b;33/272 The total flux density of J103025+052430 at 144 MHz and 1400 MHz, as well as the flux densities of the individual morphological components, are listed in Table 2, together with the respective luminosities. These were measured from the 6-arcsec resolution maps at both frequencies for consistency and using the black regions shown in Fig.…”
Section: Radio Source Propertiesmentioning
confidence: 94%
“…We stress that, while recent observational efforts are significantly increasing the detection number of giant radio galaxies and giant radio quasars (GRQs) (e.g. Kuźmicz et al 2018;Dabhade et al 2020a,b;Bruni et al 2020;Kuźmicz & Jamrozy 2021;Delhaize et al 2021;Andernach et al 2021;Simonte et al 2022;Mahato et al 2022, Oei et al 2022, the number of giant radio sources identified at redshift z > 1.5 remains to date limited (10/239 in the sample of Dabhade et al 2020b;33/272 The total flux density of J103025+052430 at 144 MHz and 1400 MHz, as well as the flux densities of the individual morphological components, are listed in Table 2, together with the respective luminosities. These were measured from the 6-arcsec resolution maps at both frequencies for consistency and using the black regions shown in Fig.…”
Section: Radio Source Propertiesmentioning
confidence: 94%
“…Recent research (Dabhade et al 2017(Dabhade et al , 2020bUrsini et al 2018;Bhukta et al 2022c) has accepted 0.7 Mpc as the lowest linear size limit of GRSs with the updated H 0 value obtained from observations. The total number of GRSs known to date is comparatively small with respect to RSs, despite the fact that their number has significantly expanded during the past 7 yr (Dabhade et al 2017;Kuźmicz et al 2018;Dabhade et al 2020aDabhade et al , 2020bDabhade et al , 2020cKuźmicz & Jamrozy 2021;Andernach et al 2021;Mahato et al 2022;Simonte et al 2022;Dabhade et al 2023). The longest known GRG to date is J081421.68+522410.0 in the LOw-Frequency ARray (LOFAR) Two-meter Sky Survey (LoTSS) Data Release 2 (DR2) field at 144 MHz, which extends 4.69 Mpc (Oei et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Giant radio galaxies (GRGs) are radio galaxies that have linear extents of more than 700 kpc or 1 Mpc, depending on definition (Willis et al 1974;Schoenmakers et al 2000a;Kuźmicz & Jamrozy 2012;Kuźmicz et al 2018). The total number of GRGs known to date is relatively small, even though over the past 20 years their number has increased substantially (Ishwara-Chandra & Saikia 1999;Schoenmakers et al 2000a;Lara et al 2000;Machalski et al 2001;Saripalli et al 2005;Machalski et al 2006;Jamrozy et al 2008;Kuźmicz & Jamrozy 2012;Dabhade et al 2017;Kuźmicz et al 2018;Dabhade et al 2020a,b,c;Kuźmicz & Jamrozy 2021;Andernach et al 2021;Mahato et al 2022). Their origin and the cause for their huge sizes are still not understood.…”
Section: Introductionmentioning
confidence: 99%